THE ROLE OF POLITICAL AND CULTURAL COOPERATION BETWEEN UZBEKISTAN AND TURKEY IN THE IMPROVEMENT OF THE ORGANIZATION OF TURKIC STATES - Khurshid Dilliyev (Western European Studies, 2024)
History clearly testifies that today the Turkic peoples are true brotherly peoples not only in terms of ethnic origin, but also in spirit. Despite all the twists and turns of historical development, these brotherly nations have been gaining their place in the rapidly changing world. In this article, the role of Uzbekistan and Turkey in the improvement of the organization of Turkic states is explained on a scientific basis. Also, attention is paid to the processes related to the political and cultural relations of the member states of this organization. The article also focuses on the issues related to the creation of favorable and attractive conditions for the expansion of trade relations between the Turkish states within the organization, and the measures for the rapid development of cooperation in the field of tourism with the Turkish states. The scientific article serves as a necessary guide for researchers and researchers studying issues related to the organization of Turkic states.
Keywords: Turkic peoples; Turkic states; cultural relations